Desenvolvimento e validação de capacitação on-line de avaliação de risco de pé diabético para enfermeiros - Sakamoto, Sabrina Ramires [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Introdução: A atualização profissional deve fazer parte da rotina dos profissionais de saúde, proporcionando uma melhoria contínua e refletindo no cuidado mais eficaz e na promoção de melhor qualidade de vida para os pacientes atendidos. Uma das áreas da saúde que mais necessita de conhecimento e atualização constante é a dos cuidados com pacientes diabéticos. Dentre as complicações desta patologia está o pé diabético, uma situação que pode levar a amputação de membros, onerando os custos na saúde pública e impactando significativamente na qualidade de vida do paciente, sendo de grande relevância as ações de rastreamento e prevenção de risco desse agravo. Objetivo: Elaborar e validar um curso de capacitação on-line para enfermeiros sobre avaliação de risco do pé diabético. Método: Trata-se de um estudo de elaboração e validação de curso on-line, utilizando a metodologia Team Based Learning (TBL), viabilizado em ambiente virtual de aprendizagem (AVA) por meio do Modular Object-Oriented Dynamic Learning Environment (Moodle), com encontro síncrono mediado pela plataforma Google Meeting, com uma carga horária total de seis horas entre atividades síncronas e assíncronas. Foram elaborados e validados um e-book e uma videoaula como materiais didáticos para o curso. A validação desses materiais foi feita por especialistas da área de design e da área de saúde utilizando o Índice de Validade de Conteúdo (IVC). Para a validação do curso, foram convidados especialistas (juízes) na área, com titulação de mestre ou superior

Introduction: Professional updating should be part of the routine of health professionals, providing continuous improvement and reflecting on more effective care and the promotion of a better quality of life for patients. One of the areas of health that most needs knowledge and constant updating is the care of diabetic patients. Among the complications of this pathology is the diabetic foot, a situation that can lead to the amputation of limbs, increasing public health costs and significantly impacting the patient's quality of life, being of great relevance as screening and risk prevention actions for this condition. Objective: To develop and validate an online training course for nurses on diabetic foot risk assessment. Method: This is a study on the development and validation of an online course, using the Team Based Learning (TBL) methodology, made possible in a virtual learning environment (VLE) through the Modular Object-Oriented Dynamic Learning Environment (Moodle), with synchronous meeting mediated by the Google Meeting platform, with a total workload of six hours between synchronous and asynchronous activities. An e-book and a video lesson were created and validated as teaching materials for the course. These materials were validated by design and healthcare experts using the Content Validity Index (CVI). To validate the course, experts (judges) in the area, with a master's degree or higher, were invited. The following were evaluated: title; courseware; methodology; evaluative activities; problem situation; clarity of information; relevance. Content validation was carried out by judges using the Content Validity Index of each item (IVCI); Content Validity Ratio (CVR); Modified Kappa coefficient (CKM); and Confidence Interval (CI), . Results: The participants was, majority female, with an average age of 42.5 years, with an average training time of 18.3 years and an average time of working on the course topic of 11.9 years. The course was well evaluated, with IVCI, CVR and CKM, presenting a score of "1.0" assigned to all items. Conclusion: The course was validated by the experts, demonstrating the relevance of educational actions for the process of continuous improvement of health care in relation to the diabetic foot.
Development and validation of online diabetic foot risk assessment training for nurses
Keywords: Capacitação profissional; Pé diabético; Cuidados de enfermagem; Estudos de validação; Ciência e desenvolvimento